2013
DOI: 10.1155/2013/357418
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Coexistence of Microwave Wireless Communication and Power Transfer Technologies for Battery-Free Sensor Network Systems

Abstract: This paper describes experimental demonstrations of a wireless power transfer system equipped with a microwave band communication function. Battery charging using the system is described to evaluate the possibility of the coexistence of both wireless power transfer and communication functions in the C-band. A battery-free wireless sensor network system is demonstrated, and a high-power rectifier for the system is also designed and evaluated in the S-band. We have confirmed that microwave wireless power transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The ES transmits continuous microwave to the DT. Note that the use of continuous microwave for MPT is a general assumption as in [3], [4], [7], [8]. We have confirmed that the bandwidth for MPT is less than 2 kHz through measurements.…”
Section: Adjacent Channel Operation Of Continuous Mpt and Wlan Data Tsupporting
confidence: 68%
See 1 more Smart Citation
“…The ES transmits continuous microwave to the DT. Note that the use of continuous microwave for MPT is a general assumption as in [3], [4], [7], [8]. We have confirmed that the bandwidth for MPT is less than 2 kHz through measurements.…”
Section: Adjacent Channel Operation Of Continuous Mpt and Wlan Data Tsupporting
confidence: 68%
“…There is much research on MPT for wireless devices. In [6], [7], the authors have succeeded in designing antennas and rectifiers. In [8], [9], the authors have succeeded in powering mobile phones or sensor devices wirelessly using the 2.4-GHz band.…”
Section: Introductionmentioning
confidence: 99%
“…The far-field WPT technique is based on electromagnetic radiation; it operates in the microwave frequency band 2.4-5.8 GHz [54]. In this technique, the same frequency band can be utilized for WPT and communication information because the WPT uses the RF signals to obtain DC energy [55].…”
Section: Frequencymentioning
confidence: 99%
“…The first type of architecture supports a SWIPT system by employing two different EM waves for information transfer and power transfer, respectively [10]. The most straightforward option is the parallel independent architecture seen in Fig.…”
Section: Different Em Wavesmentioning
confidence: 99%